2009
DOI: 10.1097/tp.0b013e3181a6b4ff
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplant From Very Old Donors: How Far Can We Go?

Abstract: Our results seems encouraging with patient and graft survival rates, complication rates, and renal function parameters being slightly worse than in expanded criteria donors, but still generally acceptable. The use of old kidneys in old recipients, bearing in mind their usual life expectancy, gives them a properly functioning kidney and improved quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 30 publications
2
19
0
4
Order By: Relevance
“…For example, Chavalitdhamrong and associates 7 found that transplants from donors aged 70 years and older were associated with a higher risk of graft loss and patient death compared with transplants from donors aged 60 to 69 years. However, Collini and associates 8 reported their experiences at an Italian transplant center where they used "ultra-old"donors (> 75 years old) with increasing graft survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chavalitdhamrong and associates 7 found that transplants from donors aged 70 years and older were associated with a higher risk of graft loss and patient death compared with transplants from donors aged 60 to 69 years. However, Collini and associates 8 reported their experiences at an Italian transplant center where they used "ultra-old"donors (> 75 years old) with increasing graft survival rates.…”
Section: Discussionmentioning
confidence: 99%
“…When stratified by recipient age, ECD kidneys from donors aged 70 years (compared to ECD 50-69 years) were associated with an increased risk of DCGF for recipients aged 41-60 years (HR 1.48, 95%CI 1.06, 2.06; p=0.02) but not for older recipients aged >60 years (HR 1.12, 95%CI 0.86, 1.46; p=0.40), suggesting that older ECD kidneys may have a smaller unfavourable impact in older recipients. In contrast, an Italian study demonstrated that 3-year graft and patient survival was similar in recipients receiving ECD kidneys from donors >75 years and <75 years (Collini, Kalmar et al 2009). This inconsistent finding may be explained by the greater use of double kidneys (from donors >75 years) in the Italian study.…”
Section: Expanded-criteria Donor (Ecd) Kidneys (mentioning
confidence: 99%
“…El principal y el primer problema con el que nos encontramos es que en la definició n de los criterios ampliados de donació n, el límite inferior de edad está claramente definido (60-65 añ os), pero no sucede lo mismo con el superior. Por lo tanto, debemos preguntarnos cuá l es la edad má xima aceptable para un donante cadá ver 5 . Un 30-40% de los )riñ ones de ECD* que en un principio se consideran aptos se termina por rechazar, sobre todo una vez valorados en la cirugía de banco y biopsiados 4 .…”
Section: Discusió Nunclassified